Sweet and bitter near-threshold solutions activate cross-modal correspondence between taste and shapes of cups. (July 2020) - Pich, Jordi; Chuquichambi, Erick G.; Blay, Nicole T.; Corradi, Guido B.; Munar, Enric
Highlights: Receptacle shape shows taste correspondence in sweet and bitter near-threshold drinks. Sweet associates to curved and bitter to sharp receptacles in specific comparisons. Confidence level of responses is higher in the bitter than in the sweet comparisons. Abstract: Recent studies have pointed out some cross-modal correspondences between flavoured beverages, as well as basic taste solutions, and specific geometric visual cues. Some of them associate known drink tastes to shapes of receptacles. In particular, sweetness is associated with curved receptacles and bitterness with sharp-angled ones. Our study aimed to test the hypothesis according to which near-threshold solutions might also activate this cross-modal correspondence. We used two different cup forms, one curved and the other sharp-angled, with pure sweet and bitter solutions just above sensorial thresholds. We designed two tasks using a two-alternative forced-choice test. Participants had to decide which drink was sweeter, Task 1, and bitterer, Task 2, from the curved and sharp-angled cups. Results showed the cross-modal correspondence but only when participants drank first from the curved cup and second from the sharp-angled cup. The effect disappeared when participants drank first from the sharp-angled cup and second from the curved cup. This suggests that the correspondence emerges using sweet and bitter near-threshold solutions in specific conditions. On the other hand, results also showed that confidence level of responses was significantly higher in the bitter task than in the sweet task. We discuss these complex results in the light of different theoretical proposals to explain this cross-modal correspondence.